Efficacy and Safety of Thalidomide As a Pre-Medication of Chemotherapy-Induced Nausea and Vomiting (CINV) Following Highly Emetogenic Chemotherapy (HEC): A Systematic Review and Meta-Analysis - Xie, Jiyi; Zhang, Cong; Li, Shijun; Dai, Rong; Sullivan, Mitchell A.; Deng, Bin; Xu, Qiling; Wang, Jinglin; Shi, Chen; Zhang, Yu (Frontiers in Oncology, 2022)
Background In China, thalidomide (THD) has been used to prevent chemotherapy-induced nausea and vomiting (CINV) following highly emetogenic chemotherapy (HEC); however, there is limited evidence on the efficacy and safety of THD in this setting. The aim of this study was to evaluate the efficacy, safety, and impact on quality of life (QoL) of THD on CINV following HEC. Methods Electronic databases were systematically searched for all randomized controlled trials (RCTs) in HEC using THD. The primary outcomes were complete response (CR) and no nausea, Secondary outcomes were the incidence of adverse events and QoL related indicators. We calculated risk ratios (RRs) and 95% confidence intervals (CIs) using a fixed-effects model. In the case of heterogeneity (I2≥50%), a random-effects model was performed. Results A total of 3168 patients were included from 34 RCTs. In terms of CR rate, THD plus 5-HT3 receptor antagonist (5-HT3RA) with or without dexamethasone (DEX) was significantly higher than 5-HT3RA with or without DEX in the acute phase (74.4% vs 67.4%; RR 1.10), delayed phase (70.6% vs 50.4%; RR 1.53), and overall phase (68.4% vs 53.4%; RR 1.28). In terms of no nausea rate, the THD group was also significantly higher than the control group in the acute phase (61.7% vs 55.5%; RR 1.12), delayed phase (50.5% vs 30.0%; RR 1.69), and overall phase (44.6% vs 29.9%; RR 1.50). There was no statistical difference in the incidence of fatigue, headache, diarrhea, rash, hepatorenal damage, and myelosuppression between those with and without THD. The incidence of increase in KPS scores, weight gain, appetite improvement, and sleep quality improvement were significantly higher with the addition of THD. Conclusions THD may be effective and safe for the prevention of CINV patients treated with HEC and may improve QoL.